Penerapan Asas Proporsionalitas Bagi Hakim dalam Mengadili Sengketa Kontrak - Teguh Harissa* (Airlangga Development Journal, 2018)
In fact the appropriateness of the contract substance is the dismissibility of the parties '  wishes in  a  contractual  relationship,  which  is based  on  agreement, proficiency, ability and compliance with statutory regulations. However, the appropriation and exegesis of the existence of a new problem, there is a double understanding, ambiguity to lead to the misinterpretation of the wishes of the contractual parties, which can cause The Parties ' rights and obligations. For this it is important to do a search of the red thread of a contract, which is expected to find the identity of a contract when disputed by the parties. In this case the principle of proportionality can be used as a parameter for judges in each level of justice in finding a win solution in the matter of the commercial contract he handled. This is because the proportionality measure of the exchange of rights and contractual obligations is always based on equitability, freedom, distribution-proportionate that is not independent of the principle of accuracy, feasibility and Fit. All of which can be used as a red thread of the true meaning of a contractual relationship, which in fact does not have to be centered on the proportion of the distribution of rights and obligations mathematically, but more than that through The basic search of proportionality by the magistrate of the judge, then any contractual matters handled will be resolved worthily and appropriately (fair and reasonableness) in order to achieve a win-win solution among the parties in dispute.